Las "Elegías" de Propercio como modelo de las "Odas" de Rodrigo de Santaella - Pascual Barea, Joaquín, 1963- (1995)
In 1504, Santaella published some variations on Propertius´elegies to praise Mary, the Mother of God. The different stylistic, semantic, syntactic and phonetic procedures used to achieve this, are exemplified in the article, which also deals with the chief purpose of adapting the themes, words, as well as metric and rhythmic patterns of the ancient love´s elegy, to these sacred odes.
Keywords: Propercio, Sexto Aurelio; Fernández de Santaella, Rodrigo, -- 1444-1509